Malawi : Rural Energy and Institutional Development - Girdis, Dean; Hoskote, Mangesh (World Bank, Washington, DC, 2014)
This study reviews Malawi's policies in the biomass, rural electrification, and non-biomass renewable energy sub-sectors to identify problems and constraints to progress and to propose policies, initiatives, and institutional structures to overcome those problems and constraints. The main recommendations of this report to the Government of Malawi are as follows: 1) reform the present legislative and regulatory framework to permit and encourage local management of woodlands on a commercially viable and environmentally sustainable basis, 2) devolve the exclusive authority and responsibility for the exploitation and management of forest cover other than that pertaining to the gazetted forests (that is, forests that are assigned or marked out by the government) to the local rural population. 3) Provide real incentives (including penalties, where applicable) for private sector tree planting, in particular on the tobacco estates. 4) apply a stumpage fee system to achieve environmental (sustainable management) and energy policy (efficient conversion and end use) objectives. 5) create a regulatory and institutional framework within which private sector initiatives and large-scale rural electrification can proceed in a financially viable manner. 6) establish a mechanism for the provision of technical assistance, promotion, and support in cases where off-grid rural electrification is to be executed by the private sector. 7) create a mechanism for the cofinancing of rural electrification. 8) Create an enabling environment within which the development and dissemination of non-biomass renewable energy sources can be accelerated. 9) provide fiscal relief (for example, remove import tariffs, and provide preferential VAT treatment on renewable energy technology systems and their components) and other incentives for the use of renewable energy sources. And finally, 10) Where cost-effective, promote the use of renewable energy in rural electrification projects, and specifically in government-sponsored rural social investments in, for example, health and education.